Mainstreaming women in post-conflict development: a case study of Liberia - Coutinho, Beatriz Azevedo (2020)
Post-Conflict development literature tends to overlook the importance of including women and gender policies in statebuilding process. I use the Liberian case as the main frame to analyze how gender development policies can enhance this process by tackling the roots of conflict. Through a qualitative analysis of Liberia\'s history, its gender and development policies, and its dual system of law, the dissertation exams president Sirleaf\'s policies and actions towards women. It demonstrates the constraints her government faced and the strategies used to overcome them. Using international institutions\' data, ground research reports, government documents, it identifies that her government experienced certain challenges to address sexual and gender-based violence crimes. Since such felonies are part of violent infrastructure that deeply affects women and their capabilities of being fully integrated socially, economically, and politically to society. Therefore, this paper aims to shine a light on the contemporary debate on Gender and Development, as well as bring a feminist approach to statebuilding analysis.